Дискретне інтегрування ДПК довільної конфігурації на основі вирахування сум - Івженко, Олександр Васильович; Ивженко, Александр Васильевич; Ivzhenko, Oleksandr; Шрамко, Олександр Володимирович; Шрамко, Александр Владимирович; Shramko, Oleksandr (My University, 2019)
UK: Дану роботу виконано в рамках дослідження питань дискретного геометричного диференціювання, коли значення похідних вибирається за умови відсутності осциляції. Зазначено, що погоджене згущення побудованих дискретно представлених кривих (ДПК) на основі інтегрально - диференціальних зв'язків та побудова точок згущення на наступному та вихідному графіку інтегралу за умови відсутності осциляції має велике значення при розв’язання задач дискретного геометричного моделювання. Пропонований метод дозволяє оцінювати змінну складову при аналізі і прогнозуванні природних явищ і процесів. Це сприяє проведенню якісного геометричного моделювання явищ і процесів на основі побудови адекватних математичних моделей. RU: Данная работа выполнена в рамках исследования вопросов дискретного геометрического дифференцирования, когда значения производных выбирается исходя из условия отсутствии осцилляции. Отмечено, что согласованное сгущение построенных дискретно представленных кривых (ДПК) на основе интегрально - дифференциальных связей и построение точек сгущения на следующем и исходном графике интеграла, при отсутствии осцилляции, имеет большое значение при решении задач дискретного геометрического моделирования. Применение квадратурных формул для построения интегральных ДПК и их сгущения способствуют уплотнению дифференциально-интегральных связей между соответствующими ДПК и повышают точность моделирования. Предлагаемый метод позволяет оценивать переменную составляющую при анализе и прогнозировании природных явлений и процессов. Это способствует проведению качественного геометрического моделирования явлений и процессов на основе построения адекватных математических моделей. Применение при этом информационных технологий дает проектировщику возможность экономии времени при проведении вычислений и позволяет усовершенствовать умение поиска информации для решения поставленной задачи. EN: The given work is executed within the framework of research of questions of discrete geometrical differentiation when values of derivatives get out at absence oscillation. The coordinated condensation of constructed discretely submitted curves (DSC) on a basis integral - differential communications and construction of points of a condensation on the following and initial schedule of integral is marked, that, at absence oscillation, is of great importance at the decision of tasks of discrete geometrical modeling. Application quadrate formulas for construction integrated DSC and their condensations promote condensation of differential-integrated communications between corresponding DSC and raise accuracy of modeling. In work the way of discrete integration DSC of an any configuration is offered by drawing up of the table of the sums on the basis of ordinates initial DSC. The proposed technique allows solving the problems of statistical data processing in different areas of activity. The developed method is based on the introduction of modern methods of analysis to solve the problem of data prediction, promotes the use of information technology. A specialist, at the same time, only research work remains setting the task, assessing the quality of the models obtained. For this, it is necessary to have appropriate training in the field of application of computer technology in the processing and analysis of statistical data. The proposed method allows to estimate the variable component in the analysis and prediction of natural phenomena and processes. This contributes to the qualitative geometric modeling of phenomena and processes based on the construction of adequate mathematical models.
Дискретное интегрирование ДПК произвольной конфигурации на основе вычисления сумм
Discrete integration DSC of an any configuration on the basis of calculation of the sums
Keywords: дискретно представлена крива (ДПК); таблиця сум; подвійний інтеграл; екстремум; інтегрально – диференціальний зв'язок; осциляція